Masks and Human Connections
XV, 355 p. 22 illus.
Keywords: "The contributors to this fascinating book highlight the manifold ways in which the symbolic meanings and practices related to mask making and wearing have changed over time. The book tells you all you need to know about the history and enduring social power of the mask." —Deborah Lupton, Professor in the Centre for Social Research in Health at UNSW Sydney, Australia. Co-author of The Face Mask in COVID Times (2021). “Masks and Human Connections is undoubtedly praiseworthy in facing the challenge of gathering and starting to articulate suggestions, studies, and interpretations concerning the new meanings of masks, with a rich variety of topics and methodologies.” —Massimo Leone, Professor of Philosophy of Communication, Cultural Semiotics, and Visual Semiotics at the University of Turin, Italy. This interdisciplinary collection explores four distinct perspectives about the mask, as object of use for protection, identity, and disguise. In part I, contributors address human identities within collective social performance, with chapters on performativity and the far right and masked identities in political resistance and communication. Part II focuses on the mask as a signifying object with strong representational challenges, exploring representations in festivals, literature, and film. Part III investigates the ambiguous use of the mask as a protective and concealing element, delving into visual culture and digital social media contexts. Finally, Part VI draws on the work of Levinas and Deleuze to investigate a philosophical view of the mask that addresses memory and ethics within intersubjective relationships. Questioning the contemporary world, using communication, sociology, visual culture, and philosophical theory, the volume provides a pedagogical and formative perspective on the mask. Luisa Magalhaes is Assistant Professor at the Catholic University of Portugal, and editor of 'Toys and Communication' (2018). Candido Oliveira Martins is Associate Professor at the Catholic University of Portugal.